Deutschland nach dem Grundvertrag - Cramer, Dettmar, 1929-2023 1929-2023 (Bonn aktuell, 1973)
Includes the text of the treaty of 21 Dec. 1972 between the Federal Republic of Germany and the German Democratic Republic.